Jim Flores, ControlTrix : a newly-installed vice-president of strategy tries to make sense of his company's human resource policies - Elias, Jaan; Flaumenhaft, Ben; Bagley, Constance E. ([London] : SAGE, 2016)
This case is written as a fictional journal by someone working in human resource management and details a number of conflicts that he encounters through his work.
Originally Published in: Elias, J., Flaumenhaft, B., & Bagley, C. E. (2008). Jim Flores, ControlTrix: A Newly-Installed Vice-President of Strategy Tries to Make Sense of His Company's Human Resource Policies. 08-015. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Personnel management -- Case studies; Strategic planning -- Case studies